Republic of Kazakhstan : Technical Assistance Report-Risk-Based Supervision Pillar 2 Implementation. (IMF Staff Country Reports; Country Report ;, 2022)
This virtual technical assistance (TA) mission supported the Agency in strengthening certain elements of its risk based supervisory framework. The mission focused on assisting the Agency with its development of internal supervisory methodologies for assessing a bank's ICAAP, and for setting individual Pillar 2 supervisory capital requirements. The mission provided recommendations and targeted training. The priorities for the next TA missions were discussed with the Agency (strengthening banking supervision and cybersecurity, and diagnostic TA of insurance sector supervision will be considered). The mission benefited from simultaneous translation.